PENGARUH CSR, KONEKSI POLITIK, RISIKO PERUSAHAAN, DAN FAKTOR LAINNYA TERHADAP AGRESIVITAS PAJAK - Putri, Audy; Rahayuningsih, Deasy Ariyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research aims to obtain empirical evidence regarding the influence of independent variables, namely capital intensity, inventory intensity, corporate social responsibility, audit committee, independent board of commissioners, company size, firm risk, political connections, debt levels, and profitability on the dependent variable, namely tax aggressiveness. The objects used in this research are companies with industrial categories in the form of consumer cyclicals and consumer non-cyclicals which are listed on the Indonesia Stock Exchange (BEI). The research period is three years, namely from 2020 to 2022. The sample used in this research was 55 companies or 165 data obtained using the purposive sampling method. Data were analyzed using multiple regression analysis. The results of this research show that the variables of company size and profitability influence tax aggressiveness. On the other hand, the variables capital intensity, inventory intensity, corporate social responsibility, audit committee, independent board of commissioners, company risk, political connections and debt levels have no influence on tax aggressiveness. Companies use CSR to gain a positive image in society, so that companies will not care about the tax burden that must be paid. Whether small or large, the tax burden is not a problem as long as the company has legitimacy from stakeholders. This means that corporate social responsibility has no effect on tax aggressiveness.